ANALISIS DAN PERANCANGAN SISTEM INFORMASI PADA BRASTAGI SUPERMARKET RANTAUPRAPAT DENGAN MENERAPKAN VIEWPOINT ORIENTED REQUIREMENT DEFINITION (VORD) BERBASIS WEB - Dyah Faramida Octaviani Lubis; Darwis Robinson Manalu; Jhoni Maslan (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Technological progress in the Millennial Era is very fast, especially in the business world, it has a very large effect. Information technology is currently growing in line with the needs of millennial children who want convenience. So every college wants to achieve a goal. So to achieve this goal, higher education institutions encourage to establish a Business Unit of the Faculty of Computer Science, Indonesian Methodist University (FIKOM UMI). Therefore we need a system that aims to improve the development of an entrepreneurial culture and improve the academic community. By overcoming these problems, a web-based millennial child accessories sales application was designed by applying the FCFS (First Come First Served) method. The millennial generation is currently a major player in the Indonesian economy. So in the business context, it is very important to understand the millennial character so that they can read product trends that are currently popular. One of the products that can show a person's character is accessories. The results obtained are intended to make it easier for customers to order and purchase a variety of accessories products and prioritize customers who are required to pay then the goods are sent and processed first. The system is built using the HTML and PHP programming languages, and the server uses Xampp and the database uses MySql.